Effect of Dry Eye Disease on Central Corneal Thickness and Corneal Topometric Indices Measured by Scheimpflug Tomography - Masoud Siyahkamari; Amir Asharlous; Ali Mirzajani; Hassan Koohian; Ebrahim Jafarzadepour; Hadi Ostadimoghaddam; Nazereh Babaei; Abbasali Yekta; Mehdi Khabazkhoob (Acta Medica Iranica, 2023)
To evaluate the effect of dry eye disease (DED) on the central corneal thickness and anterior corneal surface irregularity parameters using Scheimpflug tomography. In this study, the central corneal thickness and topometric indices of the anterior corneal surface were compared between the right eyes of 43 subjects with dry eye (DE group) and the right eyes of 35 non-dry eye individuals (NDE group). The central corneal thickness (CCT) and the topometric indices of the anterior corneal surface, including IVA, IHA, ISV, and IHD, were measured using the Pentacam HR (Pentacam-HR, Oculus, Wetzlar, Germany). Dry eye was diagnosed using a symptom questionnaire, TBUT, and Schirmer’s test without anesthesia. The mean ISV, IVA, IHA, and IHD were 17.02 3.43, 0.114 0.04, 5.82 4.82, and 0.011 0.01 in the DE group and 14.65 3.10, 0.086 .03, 3.70 3.23, and 0.007 0.00 in the NDE group, respectively. All of the above corneal irregularity indices were significantly higher in the DE group (P<0.05). The mean CCT was 531.19 µ (±34.88 µ) and 540.66 µ (±27.13 µ) in the DE and NDE group, respectively. Based on linear regression analysis, ISV, IVA, IHA, and IHD had a significant association with DED (P<0.05), while CCT had no significant association with DED (P=0.148). DED significantly increases corneal surface irregularity, but it has no significant effects on CCT measured by the Pentacam.